Optimization of Arsenic Removal from Aqueous Solution Using Indigenously Prepared Biosorbents from Fruit Peels through Response Surface Methodology - Muhammad Tauseef Azam; Asif Ahmed; Anwaar Ahmad; Azeem Khalid (Al-Qanṭara, 2024)
Sorption potential of the indigenously prepared biosorbents from orange, melon and banana peels were optimized for arsenic. The responses were generated using response surface methodology (RSM), results indicated a significant model with three sources of biosorbents was also influencing the levels of arsenic sorption significantly. The high R2 value (above 90%) indicating a good reliability of model and explained greater than 90% of variability among collected data. Linear effect of biosorbent dose concentrations (mg) were observed on the sorption efficiency for As. However, the sorption efficiency reduces significantly after the interaction time of 120 minutes. Under optimized predicted model actual experiment revealed that melon peel biosorbent uptake the 96.5mg, orange peel biosorbent uptake 83.5mg, and banana peel biosorbent uptake the 80.25mg of As. The response surface methodology showed that the indigenously prepared biosorbents had a great potential for removal of arsenic from water. And the sorption potential was greater in melon peel as compared to orange peel and banana peel respectively. Keywords: Fruit peels; Biosorbent, Heavy metals; Response surface Methodology